Future developments of a deformation-wear transition map of DLC coating - Mohd Fadzli, Abdollah (jstage, 2012)
The deformation-wear transition map of hydrogen-free amorphous carbon coating (commonly known as Diamond-Like Carbon (DLC)) is intended to graphically distinguish between the plastic deformation and impact wear of DLC coating, as well as, to predict its transition points under cyclic impact loading. In this study, besides the maximum normal impact load, other promising parameters that would induce the wear of DLC coating, have been proposed for future developments of a deformation-wear transition map. This study was carried out by impacting a DLC coated tungsten high speed steel (SKH2) disc, with a chromium molybdenum steel (SCM420) pin, at up to 105 impact cycles. All impact tests were conducted at room temperature under lubricated conditions. The preliminary results suggest that impact velocity can also contribute to the wear of DLC coating as a result of its phase transformation.